Catchment scale controls the temporal connection of transpiration and diel fluctuations in streamflow. Issue 18 (5th June 2012) - Graham, Chris B.; Barnard, Holly R.; Kavanagh, Kathleen L.; McNamara, James P.
Abstract: Diel fluctuations can comprise a significant portion of summer discharge in small to medium catchments. The source of these signals and the manner in which they are propagated to stream gauging sites is poorly understood. In this work, we analysed stream discharge from 15 subcatchments in Dry Creek, Idaho, Reynolds Creek, Idaho, and HJ Andrews, Oregon. We identified diel signals in summer low flow, determined the lag between diel signals and evapotranspiration demand and identified seasonal trends in the evolution of the lag at each site. The lag between vegetation water use and streamflow response increases throughout summer at each subcatchment, with the rate of increase as a function of catchment stream length and other catchment characteristics such as geology, vegetation and stream geomorphology. These findings support the hypothesis that variations in stream velocity are the key control on the seasonal evolution of the observed lags. Copyright © 2012 John Wiley & Sons, Ltd.